2016
DOI: 10.1080/14737175.2016.1187562
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of genetic defects of thiamine transport and metabolism

Abstract: We conducted a literature review of all reported cases with these genetic defects, and focused our paper on treatment efficacy and safety, adverse effects, dosing and treatment monitoring. Expert commentary: Doses of thiamine vary according to the genetic defect: for SLC19A2, the usual dose is 25-200 mg/day (1-4 mg/kg per day), for SLC19A3, 10-40 mg/kg per day, and for TPK1, 30 mg/kg per day. Thiamine supplementation in SLC19A3-mutated patients restores CSF and intracellular thiamine levels, resulting in succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 67 publications
0
48
0
1
Order By: Relevance
“…Thiamine doses are very variable but generally within the range of 10 to 40 mg/kg/day . Toxicity studies reported minor adverse reactions after endovenous administration such as transient local irritation, and only one major reaction consisting of generalized pruritus .…”
Section: Inborn Errors Of Metabolism Leading To Thiamine Dysfunction mentioning
confidence: 99%
See 4 more Smart Citations
“…Thiamine doses are very variable but generally within the range of 10 to 40 mg/kg/day . Toxicity studies reported minor adverse reactions after endovenous administration such as transient local irritation, and only one major reaction consisting of generalized pruritus .…”
Section: Inborn Errors Of Metabolism Leading To Thiamine Dysfunction mentioning
confidence: 99%
“…7,[44][45][46][47][48] More than 100 cases have been reported, all of them presenting with symptoms in childhood or adolescence. 2,3 Diabetes and anemia can appear as early as the neonatal period and require the administration of insulin and multiple blood transfusions. Deafness is usually the last manifestation to develop and requires cochlear implantation or hearing aids, 49 reported 32 individuals harboring SLC19A2 mutations.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations